Dampak Globalisasi terhadap Penafsiran Hadis di Era Kontemporer - Dea Puspita; Endad Musadad (Moral : Jurnal kajian Pendidikan Islam, 2025)
Globalization has had a significant impact on various aspects of life, including the realm of religion, particularly in the field of hadith interpretation. For centuries, hadith interpretation was based on historical context, established scientific methods, and the authority of scholars as the primary reference. However, the rapid and geographically boundless connection of Muslims worldwide has brought new and complex challenges. These changes have not only affected the way scholars and historians understand classical texts but have also expanded the space for discussion into the public sphere through digital technology. This research aims to examine in depth how globalization influences the process of hadith interpretation in the contemporary era. The focus of the study includes changes in methodological approaches to interpretation, shifts in understanding of classical texts, and the influence of cross-cultural interactions and the development of digital media on shaping more pluralistic religious perspectives. The rapid flow of information enables the exchange of views across countries, schools of thought, and cultures, creating opportunities for enriching insight, but also potentially giving rise to interpretations that deviate from traditional principles. The results of this research are expected to provide a more comprehensive understanding of the positive and negative impacts of globalization on hadith interpretation. On the positive side, globalization can facilitate access to literature, encourage interfaith dialogue, and revitalize the Islamic intellectual tradition on a global scale. However, on the negative side, globalization also risks the desires of scholarly authorities, giving rise to instant interpretations without a strong methodology, and increasing the potential for conflicting understandings. These findings are expected to be relevant for understanding contemporary social, cultural, and political dynamics, as well as contributing to efforts to construct contextual interpretations of hadith while remaining anchored in solid scientific principles.